Posted by **poo** on Thursday, June 10, 2010 at 1:04pm.

-d = 3 sqrt d - 2

a) {3}

b) none

c) {6}

d) {3,6}

## Answer this Question

## Related Questions

- algebra - Solve: sqrt (3)b + sqrt (2) = sqrt (7)b - 10 a) none b) (3) c) (-3) d...
- algebra - Solve: sqrt (3)b + sqrt (2) = sqrt (7)b - 10 a) none b) (3) c) (-3) d...
- math,algebra,help - Directions are simplify by combining like terms. x radiacal ...
- algebra - Solve: 8 = sqrt () y + 2 a){62} b){6} c) none d){66} And I tried to ...
- algebra - Solve: -d = 3 sqrt () d - 2 a) {6} b) {3,6} c) {3} d) none can you ...
- algebra - simplify the following radical expression: sqrt (3) * sqrt (3) a) 3 b...
- algebra - Solve: 4 sqrt (x) = 8 + 2 sqrt (x) a) (-4) b) (16) c) none d) (4) c
- algebra - solve sqrt () x + 7 = 2 sqrt () x a) none b) {3/7} c) {0} d) {7/3}
- Math Help please!! - Could someone show me how to solve these problems step by ...
- algebra - Simplify: 2 sqrt (3) + 6 sqrt(2) - 4 sqrt(3) + sqrt (2) a) 8 sqrt(2...